Uji Efektifitas Variasi Umpan Buah Flytrap Ramah Lingkungan dalam Mengurangi Kepadatan Lalat di Pasar Alang- Alang Lebar Kota Palembang Tahun 2022 - Zein, Rahma Mulya; Sari, Desri Maulina; Sunarsih, Elvi; Putri, Dini Arista (Jurnal EnviScience (Environment Science), 2022)
In the community environment, there are many insects that need to be controlled even though they cannot be completely controlled, one of which is flies. Poor sanitation conditionscan affect the presence of disease causing flies. Fly control can be done by physial-mechanical methods such as flytraps and baits to attract flies. The research method used is True Experiment with a post test only control group design design. In this study, 8 fly traps were used and were yellow in color. The baits used in this study were plantain, papaya and sweet fragrant mango. Placement of fly traps in this study at garbage dump (Tempat Pembuangan Sampah/TPS) and wet stall (Los Basah). The results showed that there was a significant difference in the number of flies with variations in bait trapped in the fly trap (p-value > 0.05). Banana bait was able to catch an average of 29 flies, papaya bait with an average of 18, and 12 mango baits. It can be concluded that banana fruit bait is the bait that catches the most flies compared to the other 2 baits and the bait that catches the least flies is flytrap without bait.Â Keyword : Flytrap, Flies, Fruit bait